Benefits of rapid deployment aortic valve replacement with a mini upper sternotomy - Chien, Siobhan (J Cardiothorac Surg, 2020)
BACKGROUND: Surgical aortic valve replacement (AVR) is currently deemed the gold standard of care for patients with severe aortic stenosis. Currently, most AVRs are safely performed through a full median sternotomy approach. With an increasingly elderly and high-risk patient population, major advances in valve technology and surgical technique have been introduced to reduce perioperative risk and post-operative complications associated with the full sternotomy approach, in order to ensure surgical AVR remains the gold standard. For example, minimally invasive approaches (most commonly via mini sternotomy) have been developed to improve patient outcomes. The advent of rapid deployment valve technology has also been shown to improve morbidity and mortality by reducing cardiopulmonary bypass and aortic cross-clamp times, as well as facilitating the use of minimal access approaches. Rapid deployment valves were introduced into our department at the Royal Infirmary of Edinburgh in 2014. The aim of this study is to investigate if utilising the combination of rapid deployment valves and a mini sternotomy minimally invasive approach resulted in improved outcomes in various patient subgroups. METHODS: Over a 3-year period, we identified 714 patients who underwent isolated AVR in our centre. They were divided into two groups: 61 patients (8.5%) were identified who received rapid deployment AVR via J-shaped mini upper sternotomy (MIRDAVR group), whilst 653 patients (91.5%) were identified who received either a full sternotomy (using a conventional prosthesis or rapid deployment valve) or minimally invasive approach using a conventional valve (CONVAVR group). We retrospectively analysed data from our cardiac surgery database, including pre-operative demographics, intraoperative times and postoperative outcomes. Outcomes were also compared in two different subgroups: octogenarians and high-risk patients. RESULTS: Pre-operative demographics showed that there were significantly more female and elderly patients in the MIRDAVR group. The MIRDAVR group had significantly reduced cardiopulmonary bypass (63.7 min vs. 104 min, p = 0.0001) and aortic cross-clamp times (47.3 min vs. 80.1 min, p = 0.0001) compared to the CONVAVR group. These results were particularly significant in the octogenarian population, who also had a reduced length of ICU stay (30.9 h vs. 65.6 h, p = 0.049). In high-risk patients (i.e. logistic EuroSCORE I > 10%), minimally invasive-rapid deployment aortic valve replacement is still beneficial and is also characterized by significantly shorter cardiopulmonary bypass time (69.1 min vs. 96.1 min, p = 0.03). However, post-operative correlations, such as length of ICU stay, become no more significant, likely due to serious co-morbidities in this patient group. CONCLUSION: We have demonstrated that minimally invasive rapid deployment aortic valve replacement is associated with significantly reduced cardiopulmonary bypass and aortic cross-clamp times. This correlation is much stronger in the octogenarian population, who were also found to have significantly reduced length of ICU stay. Our study raises the suggestion that this approach should be utilised more frequently in clinical practice, particularly in octogenarian patients.